Increasing The Literacy Skills of Tanjungpinang City’s Children through The Writing Essay Workshop about Project Implementation of Strengthening Profil Pelajar Pancasila: Peningkatan Kemampuan Literasi Anak Kota Tanjungpinang melalui Lokakarya Penulisan Esai bertema Projek Penguatan Profil Pelajar Pancasila - Siti Utari, Diah; Triregina, Igara; Marlina, Marlina; Arfa, Desmayeti (Yayasan Ahmar Cendekia Indonesia, 2024)
The Writing Essay Workshop About Project Implementation of Strengthening Profil Pelajar Pancasila became a positive activity in supporting the Merdeka curriculum policy, emphasizing the urgency of education character and 21st-century skills. This workshop realized the government assistance for the literacy community provided by The Agency for Language Development and Cultivation, Kemendikbudristek RI. PUSPA Kota Tanjungpinang was one of the beneficiaries among 340 literacy communities in Indonesia. The participants were 25 children aged 15-18 years old from several high schools in Tanjungpinang. Through this workshop, the participants were guided to build a brainstorming as a first step to writing an essay. The theme of the essay was the implementation and the overview of empirical practice about P5 in their school. It would be a constructive suggestion about project-based learning. The output of this workshop was a dummy book containing all of the participant’s essays.